Influence of porosity on the deformation behaviour of systems with nanostructured thermal barier coatings; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Moiseenko D. D.; Maksimov P. V.; Panin V. E. Viktor Evgenyevich; Sergeev V. P. Viktor Petrovich; Panin S. V. Sergey Viktorovich; Berto F. (2014, 2014)
Title screen